The Effect of Transparency and Accountability on The Quality Of Village Financial Reports (Empirical Study in Paseh District, Sumedang Regency) - Oktapiani, Dila; Yuniawati, Ayi Srie; Nurachman, Maman (Journal of Business, Accounting and Finance, 2024)
This study aims to determine the Influence of Transparency and Accountability on the Quality of Village Financial Reports in Paseh District, Sumedang Regency. The case study in this study is the village apparatus tasked with managing village financial reports. The method in this study uses a quantitative research method with a survey method. Data collection was carried out using cluster random sampling techniques by distributing questionnaires to 72 respondents as samples. The data analysis techniques used in this study are test hypothesis tests (partially), f-tests (simultaneously) using the IBM SPSS Version 25 program. The results of this study: (1) Transparency has a positive and significant effect on the Quality of Village Financial Reports, with a regression coefficient of 0.323, a Determination Coefficient value of 0.351 or 35.1%, t-count value> t-table (2.487> 1.66724) with a significant value of 0.015 <0.05. (2) Accountability has a positive and significant effect on the Quality of Village Financial Reports, with a regression coefficient of 0.472, a Determination Coefficient value of 0.427 or 42.7%, a calculated t-value>t-table (4.018>1.66724) with a significant value of 0.000<0.05. (3) Transparency and Accountability have a positive and significant effect